The Effectiveness of Fostering Children in The IIB Boyolali State Detention Center - Bryllian Erix Darmawan; M. Junaidi (Universitas Muhammadiyah Surakarta, 2024)
This study aims to examine and analyze the effectiveness of fostering for fostered children in Boyolali Class II B State Prison, The method used for research is empirical juridical, the analysis method used by the author uses qualitative methods. The process rather than carrying out punishments for violations of the law committed by the violators of the law itself. This penalty is intended to provide a deterrent effect on violations committed to make the violator not do it again. The purpose of punishment is not just to retaliate against people who have committed a criminal act, but has certain useful purposes, guidance inthis nature has been regulated in Law Number 22 of 2022 Article 50. There are three types of fostered child development, namely Education Development, Personal Developmentand Independence Development. The prison system is implemented in prisons or, but before prisoners are detained in prisons the accused are held in Rumah Tahanan Negara to await the verdict of the criminal conviction. Boyolali Class IIB detention center applies several ways to improve personality so that fostered children who will return to their parents become better and law-abiding individuals and can be accepted by the general public. The effectiveness of law in Indonesia itself is based on the use of existing rules. With the rules and can be carried out properly, it can be said to be effective. The effectiveness obtained in fostering has met the criteria with the implementation of fostering that runs properly in accordance with the provisions of the law supported by complete infrastructure facilities. What distinguishes it from previous researchers is that this study focuses on all fostering carried out in detention centers while previous researchers focus on one type of fostering carried out in prisons.